Dengue Infection Complicated by Hemophagocytic Lymphohistiocytosis: Experiences From 180 Patients With Severe Dengue. (12th June 2019) - Kan, Foong Kee; Tan, Cheng Cheng; Von Bahr Greenwood, Tatiana; Khalid, Khairil E; Supramaniam, Premaa; Hed Myrberg, Ida; Tan, Lian Huat; Henter, Jan-Inge
Abstract: Background: Globally, ~500 000 people with severe dengue (SD) require hospitalization yearly; ~12 500 (2.5%) die. Secondary hemophagocytic lymphohistiocytosis (sHLH) is a potentially fatal hyperinflammatory condition for which HLH-directed therapy (as etoposide and dexamethasone) can be life-saving. Prompted by the high mortality in SD and the increasing awareness that patients with SD may develop sHLH, our objectives were to (1) determine the frequency of dengue-HLH in SD, (2) describe clinical features of dengue-HLH, (3) assess mortality rate in SD and dengue-HLH, and (4) identify mortality-associated risk factors in SD. Methods: A 5-year retrospective single-center study in all adult patients with SD admitted to a tertiary intensive care unit in Malaysia. Results: Thirty-nine of 180 (22%) patients with SD died. Twenty-one of 180 (12%) had HLH defined as an HLH probability ≥70% according to histo score (HScore); 9 (43%) died. Similarly, 12 of 31 (39%) fulfilling ≥4 and 7 of 9 (78%) fulfilling ≥5 HLH-2004 diagnostic criteria died. Peak values of aspartate aminotransferase (AST), alanine aminotransferase, lactate dehydrogenase, and creatinine correlated to fatality (odds ratios [ORs], 2.9, 3.4, 5.8, and 31.9; all P < .0001), as did peak ferritin (OR, 2.5; P = .0028), nadir platelets (OR, 1.9; P = .00068), hepatomegaly (OR, 2.9; P = .012), and increasing age (OR, 1.2; P = .0043). Multivariable logistic regression revealed peak AST (OR, 2.8; P = .0019), peak creatinine (OR, 7.3; P = .0065), and SOFA (Sequential Organ Failure Assessment) score (OR, 1.4; P = .0051) as independent risk factors of death. Conclusions: Be observant of dengue-HLH due to its high mortality. A prospective study is suggested on prompt HLH-directed therapy in SD patients with hyperinflammation and evolving multiorgan failure at risk of developing dengue-HLH. Abstract : Patient with severe dengue (SD) may develop secondary hemophagocytic lymphohistiocytosis (HLH), which is potentially fatal but treatable. We report an SD mortality of 22% and dengue-HLH mortality ~40%. Consider prompt HLH-directed therapy in patients with, or at risk of, dengue-HLH.